1986
DOI: 10.1002/ajpa.1330700103
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination of prehistoric central California skeletal remains using discriminant analysis of the femur and humerus

Abstract: A large sample (n = 370) of Central California prehistoric skeletal remains was analyzed for sexual dimorphism of long bones using nine femoral and nine humeral dimensions. Sex of all individuals was assessed using traits of the os pubis. Discriminant analysis was done separately for the robust Early Horizon sample and the Middle/Late Horizon sample. Use of multiple variables did not produce appreciably better results over the use of several of the best variables, analyzed singly. Attention is focused on measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
85
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 7 publications
8
85
1
2
Order By: Relevance
“…Ref and lower than American black [3] and South African White [6] which is comparable with values seen in American whites [3] , Californian Samples.…”
Section: Discussionsupporting
confidence: 80%
“…Ref and lower than American black [3] and South African White [6] which is comparable with values seen in American whites [3] , Californian Samples.…”
Section: Discussionsupporting
confidence: 80%
“…Since Dwight (1904/05) pointed this out almost a century ago, the importance of the diameters of the epiphyseal parts has been accounted for by previous studies (e.g. Dittrick and Suchey, 1986). In the present study, it was further found that sexual differences are especially strong in the breadth diameters of the elbow and knee joints.…”
Section: Discussionsupporting
confidence: 70%
“…In particular, the head diameters of the humerus and femur have previously been reported as good indicators of sex (Dibennardo and Taylor, 1983;Dittrick and Suchey, 1986;Liu, 1989;Liu et al, 1989;Iscan et al, 1998;Mall et al, 2001). In the present study, these variables were not as good a discriminator as the breadths of the elbow or knee joints.…”
contrasting
confidence: 47%
See 2 more Smart Citations